Online Marketing Model for Purchase Intention on High Involvement Products Using the Theory of Planned Behavior Approach: Social Media Marketing, Online Purchase Intention, Consumer Engagement, Actual Purchases behavior, High-Involvement Products. - Rinaldi, Rinaldi; giyartiningrum, RR Eko; pratama, Yhoga (Eqien - Jurnal Ekonomi dan Bisnis, 2025)
This study aims to examine and analyze the influence of social media marketing on purchase intention and actual purchase behavior, with consumer engagement as a mediating factor for high involvement products in Indonesia. Using a quantitative research approach, a survey design was employed. The population for this study includes social media users who have made online purchases in Indonesia. The target sample size is 350 respondents, selected through purposive sampling. Data collection was conducted through online surveys using Google Forms. The research model was analyzed using Structural Equation Modeling (SEM) through AMOS 24. Findings indicate that social media marketing has a significant positive impact on consumer engagement; social media marketing significantly influences purchase intention; consumer engagement significantly affects purchase intention; consumer engagement mediates the relationship between social media marketing and purchase intention; and purchase intention significantly impacts actual online buying behavior. This study offers theoretical implications by contributing to the understanding of social media marketing, purchase intention, consumer engagement, and actual purchase behavior for high involvement products in Indonesia, and provides managerial insights for businesses aiming to optimize their social media strategies to enhance consumer purchase intention and actual behavior.